LEGAL PERSPECTIVE: MSMEs AS A SUPPORT SYSTEM FOR HALAL INDUSTRY IN FULFILLING SUSTAINABLE DEVELOPMENT GOALS IN INDONESIA - Yuanitasari, Deviana; Sardjono, Agus; Susetyo, Heru (Universitas Padjadjaran, 2024)
According to the perspective of Islamic economic law, the realization of SDGs in Indonesia can be achieved through the halal industry in the form of halal MSMEs which may affect the achievement of SDGs, especially the first, second and third goals, namely, eliminating poverty which can be realized through halal SMEs, reducing hunger with halal products, and good health and welfare based on halal and tayyib principles that is also profit oriented and community oriented which can reach more people. This article discusses the legal perspective of micro and small enterprises (MSMEs) as a supporting system for the halal industry in fulfilling sustainable development goals in Indonesia.This study is a normative legal study, that is legal research conducted by examining secondary legal materials or library materials.Micro, small and medium enterprises (MSMEs) as a support system for the halal industry in fulfilling sustainable development goals in Indonesia are clearly very important. One of the achievements in the SDGs in the economic sector is welfare and equity. The success of the equitable distribution of certified MSE products in Indonesia will help improve the visibility of halal products, making it easier for consumers to find. This will have an impact on the Indonesian economy, especially in influencing GDP growth from the halal product consumption sector. MSMEs can help realize the SDGs goals. Collaboration between MSMEs and various institutions in the halal industry is very important for the development of MSMEs in Indonesia. Perspektif hukum ekonomi Islam berpendapat bahwa industri halal, yang terdiri dari UMKM halal, dapat membantu mencapai SDGs di Indonesia, terutama tujuan kesatu, kedua, dan ketiga, yaitu menghapus kemiskinan yang dapat dicapai melalui UMKM halal, mengurangi kelaparan dengan produk halal, dan memberikan kesehatan dan kesejahteraan yang baik dan thoyyib yang berbasis halal dan thoyyib. Selain itu, industri halal harus berorientasi pada keuntungan dan berorientasi sosial sehingga dapat menghasilkan industri yang menguntungkan Artikel ini akan membahas bagaimana hukum usaha mikro dan kecil (UMK) berfungsi sebagai sistem yang mendukung industri halal dalam mencapai tujuan pembangunan berkelanjutan di Indonesia.Penelitian hukum normatif, yang meneliti bahan hukum sekunder atau pustaka, adalah jenis penelitian yang digunakan. Usaha mikro, kecil dan menengah (UMKM) adalah sistem pendukung industri halal dalam pemenuhan sustainable development goals di Indonesia yang sangat krusial. Kesejahteraan dan pemerataan kesejahteraan adalah salah satu tujuan dari SDGs. Berhasilnya sertifikasi produk UMK secara merata di Indonesia akan membantu memeratakan produk halal, membuatnya lebih mudah diakses oleh pelanggan. Hal ini akan berdampak pada ekonomi Indonesia terutama dalam hal jumlah uang yang dihasilkan oleh industri yang memasarkan produk halal. Tujuan SDG dapat diwujudkan oleh UMKM. Untuk mengembangkan UMKM di Indonesia, kolaborasi antar kelembagaan dalam industri halal sangat penting.